2015
DOI: 10.1093/humrep/dev025
|View full text |Cite
|
Sign up to set email alerts
|

Platelets are an unindicted culprit in the development of endometriosis: clinical and experimental evidence

Abstract: Financial support for this study was provided by grants from the National Science Foundation of China, a grant from the Shanghai Science and Technology Commission, support from the Key Specialty Project of the Ministry of Health, People's Republic of China. None of the authors has any conflict of interest to disclose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
130
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 112 publications
(147 citation statements)
references
References 81 publications
16
130
0
1
Order By: Relevance
“…We found recently that platelets are significantly aggregated in ovarian cysts and that activated platelets induce epithelial-mesenchymal transition (EMT) and subsequent myofibroblast activation, resulting in the acquisition of the smooth muscle cell marker, increased contractility, and increased production of collagen I (D. Ding, MSc, unpublished data, January 2015). 16 As myofibroblasts are known to be the primary extracellular matrix (ECM) secreting cells during wound healing and fibrosis, 17 our data provide evidence that endometriosis are wounds that undergo repeated tissue injury (bleeding) and repair, ultimately leading to fibrosis.…”
Section: Introductionmentioning
confidence: 83%
“…We found recently that platelets are significantly aggregated in ovarian cysts and that activated platelets induce epithelial-mesenchymal transition (EMT) and subsequent myofibroblast activation, resulting in the acquisition of the smooth muscle cell marker, increased contractility, and increased production of collagen I (D. Ding, MSc, unpublished data, January 2015). 16 As myofibroblasts are known to be the primary extracellular matrix (ECM) secreting cells during wound healing and fibrosis, 17 our data provide evidence that endometriosis are wounds that undergo repeated tissue injury (bleeding) and repair, ultimately leading to fibrosis.…”
Section: Introductionmentioning
confidence: 83%
“…Platelets aggregate in ovarian cysts and promote epithelial-mesenchymal transition, characterized by acquisition of specialized smooth muscle cell markers, such as desmin, oxytocin receptor, and smooth muscle myosin heavy chain. 28 Guo et al 46 found that fluid from endometriomas from older patients also contains significantly higher concentration of total bilirubin, ferritin, and free iron when compared to younger women. In addition, older lesions have significantly more collagen content, higher adhesion scores, and contain more viscous fluid.…”
Section: The Progressive Phenotype Of Ovarian Endometriomasmentioning
confidence: 99%
“…We have recently shown increased platelet aggregation in endometriotic lesions and there are crosstalks between endometriotic stromal cells and platelets [11]. In addition, treatment of endometriotic stromal cells with activated platelets results in the upregulation of COX-2, VEGF, MMP-9, and Bcl-2 [11].…”
Section: Introductionmentioning
confidence: 99%